Are Microforms Dead? - Sridhar, M. S. (Journal of Information and Knowledge, 2002)
The futuristic slogans like ’paperless society’. ’all-digital future’. ’marginalisation of print’ and ’microfilm technology is dead’ of few stalwarts are repeatedly and mindlessly echoed all over. An effort is made here to examine the realities of practical situations to know how far they are true. Some facts and figures are presented to enable practitioners to see it themselves. Examines whether microforms are in use and is there any future for them. Presents three cases of extensive use of microfilm technology with appropriate tables and charts to illustrate how important and how alive the technology is. Highlights suitability of microforms as archival medium and the way they are becoming integral part of digital environment. Enumerates nature and importance of technical reports and the reasons for their production in microform and how they are stored and used. An analysis of use and extensive citation of reports is also presented to break the myth that reports are marginally used and reports in microforms are negligibly used.